Irrational Land Use and Desertification in Rajasthan Desert - Mann, H S; Malhotra, S P; Shankarnarayan, K A (Annals of Arid Zone, 2016)
The prevalent land use practices, soil fertility, agricultural practice, livestock population and grazing pressure, fuel consumption etc. provide ample evidence to illustrate how the arid eco-system is slowly but inexorably degrading beyond ecological capabilities and resilience leading to a stage of entropy in the arid tracts of Rajasthan. It has been suggested that land capability (suitability) is a basic tenet of any conservation policy but such a policy should be both dynamic and flexible and commensurate with the resources.